TWENTY-FIVE YEARS OF SCHOLARSHIP ON SECOND LANGUAGE COMPOSING PROCESSES: 1976-2000 - Silva, Tony; Brice, Colleen; Kapper, Jessie; Matsuda, Paul Kei; Reichelt, Melinda (International Journal of English Studies, 2001)
This work is divided into two sections: (1) an annotated bibliography of full-length, published, (mostly) basic research on second language writing and overviews thereof, and (2) an unannotated bibliography of both basic and applied research (mostly unpublished) and commentary on second language composing. Both sections have been arranged in chronological order to allow readers to follow the development of scholarship in this area. Entries are listed alphabetically within a given year. While this bibliography is extensive, it is not meant to be exhaustive, and while the focus here is on research, many of the studies included address pedagogical matters in a substantive manner.